Dinamika Perkembangan Sejarah Masjid Agung Baiturrahman di Kota Banyuwangi Tahun 1773 – 2007 - Dea Denta Tajwidi; I Wayan Pardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2018)
Baiturrahman Great Mosque is an icon of Banyuwangi Regency. The history of the establishment of the Great Mosque of Baiturrahman is inseparable from the history of the founding of Banyuwangi, because both have very strong ties, both founded by the last Blambangan Regent and the first Regent of Banyuwangi, Mas Alit. The name Mas Alit, the first regent, was Wiraguna I who was in power in 1773-1783. This historical study aims: 1) to find out the early history of the construction of the Great Mosque of Baiturahman. 2) To find out the dynamics of the development of the Grand Mosque of Baiturahman in 1773 - 2007. This type of research is historical or historical methods. This research was conducted on July 25 to August 21, 2018 at the Baiturahman Grand Mosque in Banyuwangi Regency. Data collection methods used Observation, Interviews, Study Documents. The results of this study are the Great Mosque of Baiturrahman Mosque which was previously called the Jami Mosque 'which was founded by Mas Alit, classified as the oldest mosque in Banyuwangi Regency. The background and development of the Baiturrahman Banyuwangi Great Mosque began on December 7, 1773, based on data on waqf letters in the form of mosque architectural drawings from the Mas Alit family or Raden Tumenggung Wiraguna I, Banyuwangi's first regent for Banyuwangi Muslims. until now has undergone several renovations (development); first: 1844, second: 1971, third: 1990, and fourth: 2005.